A Dual Method to Study Motion of A Robot End-Effector (Journal of Informatics and Mathematical Sciences, 2018)
This paper presents a dual method to study motion of a robot end-effector by using the curvature theory of a dual curve which corresponds to a ruled surface generated by a line fixed in the end-effector. By using dual method, translational and angular differential properties of motion such as velocity and acceleration are determined without redundant parameters. These properties are important information in robot trajectory planning. As a practical example, motion of a robot end-effector in which a line fixed in the end-effector generates a surface of hyperbolic paraboloid is investigated.
Keywords: Curvature theory; Dual Darboux frame; Dual tool frame; Robot end-effector; Robot trajectory planning; Ruled surface